Ascensão e queda: o download de música na internet nos discursos do Portal G1 (2006 - 2013) - Juliana de Alencar Viana (2016)
Some of cultural practices on the internet were considered licit or illicit, allowed or prohibited, prescribed and not prescribed due to multiple interests, often being the cultural dispute objects and involving power relations between different social actors as artists, music industry, governments and users. These disputes can be silenced or evidenced in the discourse of the media. Thus we sought to investigate how the music download was represented in the G1 news portal discourses, from 2006 to 2013. 713 news were gathered, organized and analysed, with the software assistance Nvivo10, according to their political, cultural, social and economic aspects. The political aspects, we point out the prosecutions and convictions of users, the closing of sites and music sharing networks; opinion of artists and new legislation. In economic, we identified a wider range of goods and services; free digital music liberation in exchange for advertising revenue based on audience; increase in online music services and the emergence of musical games. In cultural aspects, we highlight the remix, own digital culture and tecnobrega as another model of production, circulation and musical consumption, while pointing joints, disputes and relations between the alternative and the mainstream. The social aspects, we note permanencies and ruptures in reciprocity on the web and new forms of social interaction by musical interest. In this study, it was noted that there is no unanimity, there is no consensus in the political approach of this practice, although the repression and punishment are in the most news found in the G1 portal and also in the government actions that tended almost always to criminalize music download practice in defence of the major labels economic interests without consider the internet users interests and the common good. Thus, among analysed news, it is seen that little space was given to ideological impugnment elements, as cyber-activists initiatives in relation to the suppression of free file sharing. In this view, the access to digital goods - which is becoming increasingly private property may represent new forms of social inclusion and exclusion, in a historic context that emerges the cognitive capitalism. It is still discussed the role of consumption, often renewed in structuring lifestyles of identity profiles that occupy the communication, sociability and businesses networks, that remain producing enough challenging research subjects whose exploitation by Leisure Studies it seems inexhaustible.